Perbandingan hukum Islam dan hukum humaniter internasional dalam perlakuan dan perlindungan terhadap tawanan perang di Irak - Ekram Prawiroputro; Suharno Suharno (Jurnal Civics: Media Kajian Kewarganegaraan, 2005)
Both Islamic Law and Humanitary Law regulate of war detainee (prisoner of war) but still have different between them. The differences are in detainee classification, codified regulation, regulation in details, explicitly sanction, possibilities to flatter detainee, and distinction of slavery ban